Oral presentation Challenges in malaria monitoring in Cyprus - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Challenges in malaria monitoring in Cyprus, Invited oral presentation, LIFE CONOPS final workshop, Chania, Greece, 15 December 2017.